The relationship between the timing of a palliative care consult and utilization outcomes for ventilator-assisted intensive care unit patients. Issue 2 (29th October 2013) - Pereira, Salonie; Kozikowski, Andrzej; Pekmezaris, Renee; Sunday, Suzanne; Mir, Tanveer; Saad, Maha; Corrado, Lauren; Wolf-Klein, Gisele
Abstract: Objective: Given the great number of chronic care patients facing the end of life and the challenges of critical care delivery, there has been emerging evidence supporting the benefit of palliative care in the intensive care unit (ICU). We studied the relationship between the timing of a palliative care consult (PCC) and two utilization outcomes — length of stay (LOS) and pharmacy costs — in ventilator-assisted ICU patients. Method: A retrospective chart review was conducted ( N  = 90). Summed pharmacy costs were compared using a paired t test before and after PCC. Spearman correlations were performed between days to PCC and ICU LOS, ventilator days, and days to death following ventilator discontinuation. Results: Number of days from admission to PCC was correlated with total days on ventilator (ρ = 0.685, p  < 0.0001) and total ICU LOS (ρ = 0.654, p  < 0.0001). Number of days to PCC was correlated with pre-PCC total medication costs (ρ = 0.539, p  < 0.0001). Median medication costs were significantly reduced after the PCC ( p  < 0.0001), from $230.96 to 30.62. Median medication costs decreased for all categories except for analgesics, antiemetics, and opioids. The number of patients receiving opioid infusion increased (37 vs. 90%) after PCC ( p  < 0.0001). Significance of results: Earlier timing for PCC in the ICU is associated with a lower LOS through quicker mechanical ventilation (MV) withdrawal, presenting a unique opportunity to both decrease costs and improve patient care.